DATA MINING UNTUK MENENTUKAN PEMILIHAN CELULAR CARD DI KOTA BATAM - Simanjuntak, Pastima; Elisa, Erlin (UNIVERSITAS PELITA HARAPAN, 2019)
Batam City is an industrial city that is on a strategic track, with locations bordering other countries, namely Malaysia and Singapore. Batam City also has a function as an international world shipping port, so that information technology, especially communication is very necessary and must be applied to the industrial world in Batam City. One of the factors of communication problems in Batam City, there are still many cellular cards that are used are not affordable for all locations because they are still using signals that have not been reached so that communication often has problems. The level of card usage by cellular customers is highly dominated by prepaid card customers. Prepaid card customers can easily move to another operator by re-registering the card. Prepaid SIM cards are now easily available everywhere at very affordable and low-cost prices. Offers from all cellular operators are as good as quality, price or service. Another challenge faced is that customers are more loyal to use cellular cards. The purpose of this study is to select celular cards in Batam City. Completion of this problem using Data mining with the Association method with a priori algorithm. With the implementation of the software using Tanagra 4.1 sorfware.